THE AMBIGUITY OF INDONESIAN CONSTITUTIONAL COURT DECISIONS CONCERNING ISLAMIC FAMILY LAW CASES - Mhd Yazid (Institut Agama Islam Negeri Batusangkar, 2022)
This article examines the decision of the Constitutional Court on polygamy and interfaith marriage in Indonesia and its relationship to the human rights principles adopted in the 1945 Constitution. After the collapse of the New Order, the state was faced with the possibility of various interpretations of Islamic law. The reform opens opportunities for the emergence of new interpretations of Islamic law legislated in Indonesia, especially after adopting human rights principles in the state constitution. This interpretation is indicated in several judicial review cases to the Constitutional Court regarding the material of Law No. 1 No. 1974. This article argues with the Islamic legal philosophy approach that the interpretation of fiqh and the interpretation of human rights principles are always debated and negotiated in Indonesia. In the case of polygamy and interfaith marriage, human rights are acceptable as long as they do not conflict with the established fiqh interpretation for the sake of state stability.